Applying implementation science to sports injury prevention - Donaldson, Alex; Finch, C. F. (British Journal of Sports Medicine, 2013)
Recent commentary in the BJSM has argued that a key challenge for future sports injury prevention is to reduce the `research to practice` gap. Unfortunately, very few examples of this type of research actually exist. In this issue, Myklebust et al describe their approach to anterior cruciate ligament (ACL) injury prevention in Norwegian Handball over the past 13 years. This is one of the first published papers on the long-term outcomes of a sports injury prevention intiative that has shown promising efficacy in controlled trials. While this paper describes an impressive intial research effort and outstanding example of long-term follow-up through an ACL Injury Surveillance Programme, it also highlights challenges associated with conducting sports injury prevention implementation research.